Turning attention to tumor–host interface and focus on the peritumoral heterogeneity of glioblastoma - Fang Wang; Jiawei Dong; Yuyun Xu; Jiaqi Jin; Yan Xu; Xiuwei Yan; Zhihui Liu; Hongtao Zhao; Jiheng Zhang; Nan Wang; Xueyan Hu; Xin Gao; et al. (Nature Communications)
Abstract Approximately 90% of glioblastoma recurrences occur in the peritumoral brain zone (PBZ), while the spatial heterogeneity of the PBZ is not well studied. In this study, two PBZ tissues and one tumor tissue sample are obtained from each patient via preoperative imaging. We assess the microenvironment and the characteristics of infiltrating immune/tumor cells using various techniques. Our data indicate there are one or more regions with higher cerebral blood flow in PBZ, which we collectively name the “higher cerebral blood flow interface” (HBI). The HBI exhibited more neovascularization than the “lower cerebral blood flow interfaces” (LBI). The HBI tend to have increased infiltration of macrophages and T lymphocytes infiltration compared with that in LBI. There are more tumor cells in the HBI than in LBI, with substantial differences in the gene expression profiles of these tumor cells. HBI may be the key area of PBZ-targeting therapy after surgical resection.